The Labor Market and its Regulation by the State Regulation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the Republic of Uzbekistan, information is being provided about the labor market and its regulation by the state and the processes of implementation of the measures developed for their regulation.